401. Short Term Outcomes in Multisystem Inflammatory Syndrome in Children (MIS-C) Related to COVID-19. (31st December 2020) - Riollano, Mariawy; Marshall, Christina L; kowalsky, shanna; Tosi, Michael; Posada, Roberto; Trachtman, Rebecca; Paniz-Mondolfi, Alberto; Sordillo, Emilia
Abstract: Background: MIS-C is a multi-system inflammatory syndrome which has been described in pediatric patients after COVID-19 since late April. Our objective is to describe the short-term outcomes of the first 15 cases with MIS-C, who presented for care to a tertiary pediatric referral center. Methods: This is a retrospective chart review of patients who met MIS-C criteria based on the New York State Department of Health case definition and who were admitted to the Mount Sinai Hospital in New York City, between April 24 and May 14, 2020. We collected clinical and laboratory data during their hospital admission and subsequent outpatient follow up. Results: The range of the length of hospital stay was 6–13 days (mean=7 days). One patient expired on day 9 of hospitalization. At the time of discharge, all patients had normalization of inflammatory markers. All patients were discharged on anticoagulation therapy for 14 days. One patient was readmitted with a subdural hematoma at day 13 post discharge and 3 patients had bruising at their follow up visit 7–12 days after hospital discharge. All patients had normalization of cardiac enzymes prior to hospital discharge. Abnormalities in coronary arteries and cardiac function which were observed during hospitalizations in 4 (27%) and 8 (53%) patients respectively, had resolved by day 6–35 post discharge (mean=20 days). Conclusion: Although patients with MIS-C can present with severe multi-organ involvement and shock, the majority of the patients in our experience had resolution of symptoms and normalization of laboratory parameters within a few weeks of initial symptoms. Our findings underscore the need to carefully weigh the risk and benefits of anticoagulation therapy and to monitor this treatment closely. Further research is needed to determine long-term outcomes of these patients. Disclosures: All Authors : No reported disclosures